1998
DOI: 10.1016/s0022-2143(98)90060-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxygen free radicals in cisplatin-induced acute renal failure in rats

Abstract: We examined the role of oxygen free radicals in cisplatin-induced acute renal failure (ARF). The intravenous injection of cisplatin (5 mg/kg body weight) induced an increase in serum creatinine and tubular damage in the outer stripe of the outer medulla in rats. The renal content of malondialdehyde (MDA) transiently increased. Treatment with the free radical scavengers dimethylthiourea (DMTU) or lecithinized superoxide dismutase (L-SOD) attenuated the increase in serum creatinine. The beneficial effect of DMTU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
167
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(185 citation statements)
references
References 23 publications
13
167
1
3
Order By: Relevance
“…29,30 In the present study, an increment in MDA, a highly reactive compound and remarkable marker for oxidative stress and a decrement in GSH-Px and SOD activities, which are key antioxidants, were found in the liver of rats treated with cisplatin. After understanding the possible role of free radicals incispaltin-induced oxidative liver damage, several agents were added to the therapy as an adjuvant supplement and they attempted to protection and/or to prevent the side effects of chemotherapeutics.…”
Section: Discussionsupporting
confidence: 58%
“…29,30 In the present study, an increment in MDA, a highly reactive compound and remarkable marker for oxidative stress and a decrement in GSH-Px and SOD activities, which are key antioxidants, were found in the liver of rats treated with cisplatin. After understanding the possible role of free radicals incispaltin-induced oxidative liver damage, several agents were added to the therapy as an adjuvant supplement and they attempted to protection and/or to prevent the side effects of chemotherapeutics.…”
Section: Discussionsupporting
confidence: 58%
“…This decreased activity may be due to loss of copper and zinc, which are essential for the enzyme activity or reactive oxygen species-induced enzyme inactivation. 27) Recent evidences 2,4,24) have indicated that the free radicals and reactive oxygen species are involved in the CDDP-induced oxidative stress because of depletion of the GSH concentration and decreased antioxidant enzyme activity in the kidneys. These observations also support the hypothesis that part of the mechanism of nephrotoxicity in the CDDP-treated animals is related to depletion of antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated the direct cytotoxic mechanisms of cisplatin including DNA damage (Leibbrandt et al 1995;Ries et al 1986), mitochondrial dysfunction (Sugiyama et al 1989), formation of reactive oxygen species (ROS) (Matsushima et al 1998), and caspase activation (Kaushal et al 2001). In particular, cisplatin ototoxicity occurs primarily in the cochleae, especially in the outer hair cells (OHCs) of the organ of Corti.…”
Section: Introductionmentioning
confidence: 99%